The Legal Constitution of the European Union - Herber, Franz-Rudolf (European Scientific Journal, ESJ, 2018)
World War II (1939 – 1945) was a catastrophe for the whole world and for Europe in particular. It is one of the great miracles of the 20th century that the West European war parties did draw a line and founded an economic alliance for coal and steel production. This economical alliance is based on common values and on the rule of law. A main problem of the European Union is to give a democratic legitimation to the European institutions. It is good that e.g. the European Parliament is elected directly, it is bad that e.g. the President of the European Commission is not elected directly. In some Member States of the European Union common values and common interests are only partim shared. The people of Great Britain did decide in 2016 to leave the European Union; according to the legal constitution of the European Union a leave is allowed. The main achievement of the European Union is the abolition of inter-European taxes and thus the promotion of economical relationships between the Member States of the European Union. The Euro that is the currency of (only) some Member States has become a global player.